Investigating the Effect of Plant Growth-Promoting Rhizobacteria (Pseudomonas putida R112) on Essential Oil of Rosmarinus officinalis L. under Irrigation of Urban Purified Wastewater - Reza Dehghani Bidgoli; Mona Ghiaci Yekta (Institue of Medicinal Plants, ACECR, 2019)
Background: Environmental factors and biological regulators have effects on plants morpho-physiological and phytochemical charecteristics. Objective: The aim of this study was to investigate the growth and yield of Rosmarinus officinalis in coexistence with plant growth-promoting rhizobacteria (PGPR) under purified urban wastewater. Method: This study was done in research greenhouse of University of Kashan, Iran, on the base of factorial experiment in as a randomized complete block design (RCBD) with four replications. The treatments included PGPR (Pseudomonas putida strain R112) in two levels of inoculation and non-inoculation and also, urban purified wastewater treatment at five levels of 0 (control), 25, 50, 75, and 100 % v/v. Results: The highest fresh and dry weight of aerial parts were obtained in plants inoculated with bacteria and irrigation control treatment, as well as in the least in non-inoculated plants and irrigation with 100% purified wastewater. The fresh and dry weights of aerial parts decreased by 53.44% and 71.35%, respectively, compared to plants inoculated with bacteria and non-use of treated wastewater. Also, the highest percentage of rosemary essential oil was related to treatment of inoculated plants with 50% treatment of wastewater. Conclusion: The growth and yield of rosemary decreased with increasing the percentage of wastewater and inoculation with plant growth promoting bacteria increased the plant tolerance.